Carbon nanotube field emitter - Saito, Yahachi (Journal of nanoscience and nanotechnology, 2003)
Recently, carbon nanotubes (CNTs), possessing excellent properties as field emitters, are attracting considerable attention as electron emitters of a cold cathode. In this review article, field emission phenomena of carbon nanotubes with various morphologies and surfaces (clean surface or adsorbed molecules on it) revealed by field emission microscopy are first described. Then, the main subject of this article, application of CNTs as electron sources in display devices is reviewed. Other electric devices utilizing CNT-field emitters are also presented.